2013
DOI: 10.1038/srep02699
|View full text |Cite
|
Sign up to set email alerts
|

Anti-LRP/LR specific antibodies and shRNAs impede amyloid beta shedding in Alzheimer's disease

Abstract: Alzheimer's disease (AD) is the most prevalent form of dementia. The amyloid beta (Aβ) peptide is the predominant candidate aetiological agent and is generated through the sequential proteolytic cleavage of the Amyloid Precursor Protein (APP) by beta (β) and gamma (γ) secretases. Since the cellular prion protein (PrPc) has been shown to regulate Aβ shedding, we investigated whether the cellular receptor for PrPc, namely the 37 kDa/67 kDa Laminin Receptor (LRP/LR) played a role in Aβ shedding. Here we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…LAMR has been found to contain irregular oxidative modifications in a small‐scale proteomics investigation of the brains of Alzheimer's model mice (Shin et al, ). Modulation of LAMR has also recently been reported to affect Aβ cytotoxicity (Da Costa Dias et al, ) and its release from cells (Jovanovic et al, , ).…”
Section: Disease and Therapymentioning
confidence: 97%
“…LAMR has been found to contain irregular oxidative modifications in a small‐scale proteomics investigation of the brains of Alzheimer's model mice (Shin et al, ). Modulation of LAMR has also recently been reported to affect Aβ cytotoxicity (Da Costa Dias et al, ) and its release from cells (Jovanovic et al, , ).…”
Section: Disease and Therapymentioning
confidence: 97%
“…Initial reports suggested not only co-localisation between LRP/LR and β-secretase on the cell surface, but also that these two proteins interacted, as shown by co-immunoprecipitation [22]. The findings presented in Figures 3 and 4 help to further understand the nature of the possible interactions between β-secretase and LRP/LR, where the maximum intensity projection (Figure 3A) constructed from Z-stack images (Figure S2 in File S1) shows strong co-localisation between the 2 proteins within the cellular cytoplasm – this most likely occurring in the endosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Jovanovic et al [99] found that treating cells with anti-LRP/LR-specific antibody IgG1-iS18 or anti-LRP shRNA resulted in a significant reduction in Ab levels in comparison to the controls (Figure 4). Since it is the overproduction and aggregation of Ab that leads to the development of AD pathology, these results were of great interest, since they revealed a role for LRP/LR in the processes leading to Ab generation, and hence a possible target for future therapeutic strategies.…”
Section: The Role Of Lrp/lr In Admentioning
confidence: 92%